Campanas - Campana, Fernando; Campana, Humberto (Sao Paulo, SP, Brazil : Bookmark, 2003)
de gebroeders Campanas zijn afkomstig uit Brazilë; hun ontwerpen en materiaalgebruik refereren vaak aan het straatleven; citaat van de Edra website: Born in the province of Sao Paolo in 1961, Fernando Campana attended a course in Industrial Design at the Brazilian Museum of Sculpture after graduating from university. Born in the province of Sao Paolo in 1953, Humberto Campana also followed a course in Industrial Design at the Brazilian Museum of Sculpture after graduating in law. Together they began to work in the field of artistic design, taking part in international exhibitions and workshops with pieces they had made by hand. Among their most important solo exhibitions, we can cite The Uncomfortables in Sao Paolo in 1989, Retrospective in Rio de Janeiro in 1999, Never Letting the Poetry Escape at the Tama in Tel Aviv in 2003, Personale at the Banco do Brasil Cultural Centre in Brasilia in 2003 and in Lisbon as part of Experimenta as well as in Stockholm.^
In 2004 they created their Ideal House for the Cologne Exhibition and Convention Centre. Again in 2004, the Design Museum of London paid homage to the pair with the Zest for Life exhibition. Their work has also been seen along with other designers’ work in important exhibitions such as Project 66 in 1998 at the Moma in New York, and Air en Forme at the Museum of Design and Applied Arts in Lausanne. Again in the year 2000, they took part in the Saint’Etienne Biennial exhibition, and in Blow Up at the Vitra Design Museum in Berlin. In 2002 their work was seen in the Milano in a Van exhibition held at the Victoria and Albert Museum in London. In 2008 they recived the prestigious Design of the Year Award at Miami Art Basel, and in 2012 Designer of the Year Award by Maison & Object in Paris.From 1997 they worked with Edra for which they have designed some of their most successful creations/furnitures such as Vermelha, Boa, Favela, Corallo, Scrigno and Cipria.^
They have also worked with other firms such as Alessi, Swarovski, Venini and Vitra. They designed accessories and clothing collections for Meliss, Lacoste and Louis Vuitton. Their work is displayed in some of the world’s most important museums, among others MoMA in New York and Musée des Art Decortives in Paris.In 2011 they collaborated with Edra to redesign and refurbish the Cafè the l’Horologe at Musée d’Orsay. In 2012 they were honored with the Colbert Award for Creation & Heritage.
Engels
Portugees
Italiaans
boek
Keywords: Campana, Humberto; Campana, Fernando; Edra; eigen tijd; Brazilië